Variability in pediatric and neonatal organ offering, acceptance and utilization: a survey of Canadian pediatric transplant programs and organ donation organizations - Lee, Laurie A.; Okpere, Augustina; Martin, Dori-Ann; Mahoney, Meagan; James, Lee; Avitzur, Yaron; Piggott, Bailey; Tomlinson, Christopher; Urschel, Simon; Hamiwka, Lorraine (Frontiers in Transplantation, 2024)
IntroductionSolid organ transplantation in children is a lifesaving therapy, however, pediatric organ donation rates remain suboptimal.MethodsWe conducted a cross-sectional survey of Canadian organ donation organizations (ODOs) and pediatric transplant programs (TPs), aiming to describe policies and practices for pediatric organ allocation, acceptance, and utilization in Canada.ResultsResponse rates were 82% and 83% respectively for ODOs and transplant programs comprising 7 kidney, 3 heart, 2 lung, 2 liver and 1 intestine programs. All 9 ODOs reported offering pediatric organs following death by neurological criteria (DNC), while 8 reported offering organs following death by circulatory criteria (DCC) for some organs. Variability was found across ODOs and TPs. There was little agreement on both absolute and organ-specific donor exclusion criteria between ODOs. There was further disagreement in organ specific acceptance criteria between ODOs and TPs and between TPs themselves. Notably, despite the development of pediatric donation after DCC guidelines, organs from DCC donors are excluded by many ODOs and TPs.DiscussionFurther variability in pediatric specific training, policies, and allocation guidelines are also documented. Significant areas for improvement in standardization in organ acceptance, offering, and allocation in pediatric donation and transplantation across Canada were identified.